The Projection of the Double in Mary Shelly’s Frankenstein - Bhandari, Sabindra Raj (Pursuits: A Journal of English Studies, 2022)
The objective of this study is to explore the motif of the double in Mary Shelley’s Frankenstein. The double (double goer or alter ego) is the psychic counterpart of a person. Since it stands for psychological projection, it also reveals the darker side of one’s psyche. The monster in Shelley’s novel resembles the double of its protagonist Victor Frankenstein. What Victor cannot show and reflect in the reality has been transformed in the actions of the monster. The monster becomes Victor’s disguises self because it mirrors the deepest psychic instincts of Victor Frankenstein. Likewise, the monster claims that it is Victor’s Adam. Victor’s disguised self has been transferred in every action and dialogue related to the Monster. The whole novel centers around this pivotal point. More than that, the novel implements the narrative structure known as mise en abyme, which imbeds one story within another one. This embedding instantiates the theme of structural double and series of reflections in the novel. The novel implements the paradigm of qualitative research and the concepts of the double as a theoretical lens to expose all these issues of the double in the novel.